Ninth Five Year Plan 1997-2002 and Annual Plan 1997-98 Draft Proposals Volume II Part-I Agriculture and Allied Services - Planning Commission (Planning Commission, 1977)
The economy of Meghalaya is basically agrarian as it is rural based with Agriculture playing a predominant role of the State’s economy. The progress of the Agricultural Sector, however, continues to be handicapped by slow changing old methods of technology and large scale of shifting cultivation (Jhuming) which resulted in fluctuating agriculture productivity. The cultivated area of total geographical area 01 the Stale is about 9% on tile average during the past live years. the gross cropped area is 2.39 lakh hectare* (provisional) while the net cropped area is about 2.0) lakh hectares in 1994-95. A target of gross cropped area of 2.49 lakh hectares is proposed for the year 1996-97 against the anticipated gross cropped area of 2.43 lakh hectares and net cropped are of about 2.00 lakh hectares during 1995-96.
Planning Department Government of Meghalaya